Carta de Roberto H. Todd a Antonio R. Barceló - Todd, Roberto H.; Barceló, Antonio R. (My University, 1931)
Recomendación de Julio Francis como profesor de inglés.
Keywords: Francis, Julio; Barceló, Antonio R., 1868-1938; Colom, José Enrique; Puerto Rico. Department of Transportation and Public Works